CBT supervision behind closed doors: Supervisor and supervisee reflections on their expectations and use of clinical supervision. Issue 4 (12th August 2022) - Roscoe, Jason; Taylor, Julie; Harrington, Rufus; Wilbraham, Susan
Abstract: Objective: Previous surveys examining the routine practice of cognitive behavioural therapy (CBT) supervision have consistently found that methods utilised by supervisors often drift from expert recommendations. Harmful or ineffective supervision are two potential consequences of practices which overlook one or more of the normative, formative or restorative functions. Given that most of the research to date in this area has used quantitative methods, it is important to gain a deeper understanding of the reasons why everyday supervision differs so greatly. One way of achieving this is through exploring the "lived experience" of supervisors and supervisees. Method: Semi‐structured interviews were conducted with ( N = 10) supervisors and supervisees, and data were analysed using interpretative phenomenological analysis. Results: Three superordinate themes were identified: " inconsistency of approaches, " "autonomy" and "the relationship." The findings revealed that supervisors are practicing very differently from one another, despite awareness of expert guidance. There were some indications of supervisory drift, characterised by supervisor resistance to hierarchical structures and supervisee avoidance due to concerns about their safety within the relationship. Conclusion: Further research is needed to better understand how supervision dyads can identify and manage dysfunctional supervision practices.